Mastitis impact on high-yielding dairy farm’s reproduction and net present value - Borş, Alina; Borş, Silviu-Ionuț; Floriștean, Viorel-Cezar (Frontiers in Veterinary Science, 2024)
Poor udder health can have a negative impact on milk production and reproductive performance, which reduces the net present value (NPV) of dairy farms. The aim of this study is therefore to investigate the relationship between clinical mastitis and NPV and the financial impact of impaired reproductive function. For this purpose, 473 dairy cows were included in our study, 146 cows with clinical mastitis (CM group) and 327 clinically healthy cows (CH group) from a high-yielding dairy farm from Romania, milking around 780 dairy cows with an average milk production of 46 kg milk/day. We found that, in contrast to CH cows, CM cows had a significantly lower conception rate at first service (58.2% vs. 41.7%, P < 0.05), third service (45.3% vs. 30.2%, P < 0.05), and total services (49.2% vs. 36.4%, P < 0.05). However, this positive effect was not observed for the average days open, which were significantly lower in CM cows than in CH cows (112 ± 4.3 days vs. 142 ± 3.1 days, P < 0.05). The fact that the non-pregnant CH cows had higher somatic cell counts (> 400,000 SCC/mL) in their milk around artificial insemination (AI) and one month earlier than the pregnant cows (< 250,000 SCC/ml) supports the idea that poor uterine health affects the reproductive activity of high yielding cows. However, by using the UW-DairyRepro$ decision support tool, we found that despite the impairment of reproductive function in dairy cows, the largest negative impacts on NPV are still the cost of milk loss (US$14,439.4/farm/year), and treatment costs (US$4,380/farm/year). The costs associated with poor reproductive function in CM group (US$3,577/farm/year) we considered as an additional cost of mastitis. Finally, it appears that the impact of mastitis on reproduction is associated with a lower chance of conception than it is with a daily risk of services.